Capacity Building for a New Multicenter Network Within the ECHO IDeA States Pediatric Clinical Trials Network - Annett, Robert D.; Bickel, Scott; Carlson, John C.; Cowan, Kelly; Cox, Sara; Fisher, Mark J.; Jarvis, J. Dean; Kong, Alberta S.; Kosut, Jessica S.; Kulbeth, Kurtis R.; Laptook, Abbot; McElfish, Pearl A.; et al. (Frontiers in Pediatrics, 2021)
Introduction: Research capacity building is a critical component of professional development for pediatrician scientists, yet this process has been elusive in the literature. The ECHO IDeA States Pediatric Clinical Trials Network (ISPCTN) seeks to implement pediatric trials across medically underserved and rural populations. A key component of achieving this objective is building pediatric research capacity, including enhancement of infrastructure and faculty development. This article presents findings from a site assessment inventory completed during the initial year of the ISPCTN. Methods: An assessment inventory was developed for surveying ISPCTN sites. The inventory captured site-level activities designed to increase clinical trial research capacity for pediatrician scientists and team members. The inventory findings were utilized by the ISPCTN Data Coordinating and Operations Center to construct training modules covering 3 broad domains: Faculty/coordinator development; Infrastructure; Trials/Research concept development. Results: Key lessons learned reveal substantial participation in the training modules, the importance of an inventory to guide the development of trainings, and recognizing local barriers to clinical trials research. Conclusions: Research networks that seek to implement successfully completed trials need to build capacity across and within the sites engaged. Our findings indicate that building research capacity is a multi-faceted endeavor, but likely necessary for sustainability of a unique network addressing high impact pediatric health problems. The ISPCTN emphasis on building and enhancing site capacity, including pediatrician scientists and team members, is critical to successful trial implementation/completion and the production of findings that enhance the lives of children and families.